Origami Pump Actuator Based Pneumatic Quadruped Robot (OPARO) - Kim, Yeunhee; Lee, Yeonseo; Cha, Youngsu (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
In this study, we proposed an origami pump actuator based pneumatic quadruped robot (OPARO). The robot was constructed with a four-leg system controlled by only two motors. Specifically, the forelegs and hindlegs are pneumatically coupled to operate simultaneously with a tendon-driven system. The forelegs simultaneously performs pumping and actuating to supply air to the hindlegs, and the hindlegs are passively actuated by the air supply from the forelegs. We conducted a series of experiments to evaluate the mobility performance of OPARO. We measured the posture of each leg and analyzed the movement to determine the operating mechanism in locomotion. The motion, gait, and repeatability of OPARO were analyzed from the experimental results. Additionally, we conducted a parametric study to determine the tendencies at different gait frequencies and motor inputs. The OPARO moves at a maximum velocity of 0.11 body length per second (10.29 mm/s). Furthermore, we evaluated the gait velocity with various gait patterns according to different duty ratios and floor surfaces. Moreover, the steering performance of OPARO was demonstrated. We found that the tendon-driven pneumatic origami pump actuator system is adequate for a quadruped robot without an external air supply system.